Prevalence of potentially inappropriate medication in hospitalized elderly patients by using explicit criteria - C. Galán Retamal; R. Garrido Fernández; S. Fernández Espínola; A. Ruiz Serrato; M. A. García Ordóñez; V. Padilla Marín (Farmacia Hospitalaria)
Introduction: Potentially inappropriate medication (PIM) prescribing in older adults is quite prevalent and is associated with an increased risk for adverse drug events, morbidity, and utilization of health care resources. The aim of this study was to determine the prevalence and type of PIM in polypharmacy elderly patients on admission and discharge and the factors associated with their prescription. Just as the applicability of various explicit criteria selected from the literature and adapted to our area. Methods: We performed a cross-sectional study for 12 months (March 2010-February 2011) on 179 polypharmacy elderly patients admitted to an Internal Medicine Department. We created a list of 50 PIM using a Delphi approach based on previous published criteria (Beers, Stopp, BMC and Priscus). Through patient interviews, review of medical records and discharge reconciliation report, we identified the prevalence of PIM in the patients. We also analyzed the relationship between different factors and the prescription of PIM. Results: The prevalence of patients with PIM on admission and discharge were 71% and 48%, respectively. Out of the 50 selected PIM, 27 and 26 were detected on admission and discharge, respectively (55.5% and 57.69% included on STOPP criteria). We detected two factors associated with PIM prescription at discharge: severe-total dependence (OR = 1.8) and prescription of more than 11 drugs (OR = 2). Conclusions: PIM prevalence in our population is very high (70%), especially at hospital admission. These findings support the need for measures aimed at improving the quality of prescriptions, especially on dependent patients with polypharmacy